Peran Teknologi AI dalam Mengoptimalkan Pengambilan Keputusan dalam Pengembangan Bisnis - Rusdi Hidayat; Indah Respati Kusumasari; Zika Aisyantus Sophia; Devina Rahma Puspita (Lembaga Pengembangan Kinerja Dosen, 2024)
In the midst of increasingly rapid technological developments, Artificial Intelligence (AI) technology has also been formed as a form of development. The presence of AI technology helps many people complete their work. Including strategic activities in the decision-making process for business development. This research aims to discuss the role of artificial intelligence technology in improving decision making in the business development process by focusing on the Management Information Systems (SIM), Micro, Small and Medium Enterprises (MSMEs), and finance sectors. With a literature review used as a comprehensive research method, it involves collecting and analyzing articles related to the topic from various academic sources. The research results show that Artificial Intelligence (AI) can improve the efficiency and accuracy of decision making through in-depth analysis and algorithm-based predictions. In the Management Information Systems (MIS) sector, artificial intelligence contributes to business automation processes and information management, in the MSME sector, artificial intelligence helps in understanding consumer behavior and market trends. Meanwhile, in the financial sector, AI plays an important role as a risk analyst, financial manager and investment manager. This research is expected to provide knowledge for corporate organizations about the role of artificial intelligence technology in improving the decision-making process.